A Conceptual Model on the Relationships between Business Strategy, Business Model Innovation, Resource Configuration and Performance - Fontana, Avanti; Zubaedah, Siti Yasmina (Jurnal Manajemen Teknologi, 2012)
AbstractThe main objective of this study is to develop a research framework for strategic management researchers to develop sound strategic business model innovation that has practical implication on how to innovate firms' business models. The research identifies factors attributing to effective business model: business strategies, type of business model innovations and types of resource configurations. This study framework can guide leaders and managers to acquire the appropriate capability of coping with business model dynamics as well as major transformation that arises from business model innovations. In addition, the study provides insightful contributions in explaining the influence of business strategies (defender, prospector, analyzer) on business model innovations and firm resource configuration, and their influence on business model effectiveness. This study model is valuable considering the limited amount of empirical work previously done on the topic in question. Based on a case-study research survey in seven companies in Indonesia that took place in 2011-2012, we have drawn first conclusions expressed in four research propositions that deem further tests. One case (Food Co.) is highlighted for the description of the study to show some presence and absence of alignment between business strategy, business model innovation, and resource configuration.Keywords: effective business model, business model innovation, business strategy, defender, prospector, analyzer, resource configurationAbstrakTujuan studi ini adalah mengembangkan rerangka penelitian strategi dan inovasi model bisnis. Riset ini mengidentifikasi faktor-faktor yang mempengaruhi efektivitas model bisnis, yaitu strategi bisnis, tipe inovasi model bisnis, dan tipe konfigurasi sumber daya. Rerangka studi ini memberi perspektif kepada pemimpin dan manajer dalam bagaimana memperoleh dan membangun kapabilitas yang sesuai untuk menghadapi dinamika model bisnis dan transformasi model bisnis. Studi ini juga berkontribusi dalam menjelaskan pengaruh strategi bisnis (defender, prospector, analyzer) terhadap inovasi model bisnis, konfigurasi sumber daya, dan pengaruhnya pada efektivitas model bisnis. Studi ini penting mengingat masih terbatasnya studi empiris yang melihat keterkaitan strategi bisnis, inovasi model bisnis, konfigurasi sumber daya, dan efektivitas model bisnis. Satu ilustrasi kasuistik (Food Co.) dalam tulisan ini menggambarkan hadirnya dan ketiadaan kesesuaian antara strategi bisnis, inovasi model bisnis, dan konfigurasi sumber daya. Berbasis pada survei riset studi kasus tujuh perusahaan di Indonesia yang dilakukan pada 2011-2012, penulis menyampaikan simpulan-simpulan awal dalam empat proposisi penelitian dan saran kajian lebih lanjut.Katakunci: efektivitas model bisnis, inovasi model bisnis, strategi bisnis, tipologi strategi bisnis, konfigurasi sumber daya